1997
DOI: 10.1037/0735-7028.28.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches to assessment and treatment of persons with serious mental illness.

Abstract: Psychologists increasingly have the opportunity to work with persons with serious and chronic mental illnesses. Managed care encourages services that rely less on hospital treatment and more on a combination of brief and intensive outpatient therapy and long-term, low-cost maintenance and support. Diagnostic practices needed to be effective in such an environment include categorical and functional assessment. Psychological treatments that have been demonstrated effective include cognitive-behavioral social ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 66 publications
(53 reference statements)
2
32
0
Order By: Relevance
“…schizophrenia, bi-polar and schizoaffective disorder). The grouping of these disorders are consistent with previous conceptualizations of disorder duration and severity (Bedell et al, 1997).…”
Section: Types Of Homework 17supporting
confidence: 89%
See 1 more Smart Citation
“…schizophrenia, bi-polar and schizoaffective disorder). The grouping of these disorders are consistent with previous conceptualizations of disorder duration and severity (Bedell et al, 1997).…”
Section: Types Of Homework 17supporting
confidence: 89%
“…Nurses, psychologists, social workers, occupational therapists and welfare workers all commonly work within community mental health teams and bring discipline specific skills to the case management approach. For example, nurses play a major role in supporting medication adherence (Coombs, Deane, Lambert, & Griffiths, 2003), psychologists are utilised to conduct specific counselling interventions (Bedell, Hunter, & Corrigan, 1997) and occupational therapists may assist with ensuring that the individuals living situations are adequate (Luboshitzky & Gaber, 2000). There is also a great deal of skill and task overlap, where case managers will be required to provide a variety of generic case management activities.…”
Section: Types Of Homeworkmentioning
confidence: 99%
“…In accordance with the literature on skills training for psychiatric patients, Life Skills is perceived as most beneficial in the interpersonal realm, increasing individuals' social functioning in a variety of situations (Bedell et al, 1997;Benton & Schroeder, 1990;Dilk & Bond, 1996;May et al, 1985;Pratt & Mueser, 2002). Not surprisingly, many participants indicated that the poor attendance of other students, the videotaping of exercises, and discomfort with role-playing exercises were problematic aspects of their Life Skills experiences.…”
Section: Discussionmentioning
confidence: 54%
“…Social skills training has been described as the ''single most important innovation for the psychological treatment of persons with serious mental illness'' (Bedell, Hunter, & Corrigan, 1997, p. 220). Empirical studies have consistently shown that social=life skills training programs are effective in improving targeted skills, enhancing social functioning, increasing patients' level of assertiveness, reducing the severity of psychiatric symptoms and the length of stay at a psychiatric hospital (Bedell et al, 1997;Benton & Schroeder, 1990;Dilk & Bond, 1996;May et al, 1985;Reddon et al, 1996Reddon et al, , 2008. In a rigorous meta-analysis of 68 studies regarding skill training effectiveness for individuals with severe mental illness, Dilk and Bond (1996) concluded that behavioral skills training is effective for teaching interpersonal and assertiveness skills, either within a hospital setting or in the community.…”
mentioning
confidence: 99%
“…This method is almost identical to that employed in cognitive-behavioural family therapy and has much in common with that used in the evidence-based cognitive-behavioural treatment of depression, the prevention of self-harm, social skills training and cognitive behavioural marital therapy (Bedell et al, 1997). However, the main differences are in the training methods.…”
Section: Phase Fourmentioning
confidence: 97%